Investigating Urinary Complications in Young Infant Surgical Patients with Indwelling Epidural Catheters: A Retrospective Cohort Study - Mihaela Visoiu; Dahye Park; Erin E. Simonds; Senthilkumar Sadhasivam (Children)
Background/Objectives: Continuous epidural analgesia (CEA) is commonly used to manage postoperative pain in young infants. However, it can impair bladder function, leading to postoperative urinary retention (POUR) and necessitating Foley catheter placement, which carries a risk of urinary tract infection (UTI). Limited research exists on the frequency of POUR and UTIs and factors influencing optimal Foley catheter management in this population. Methods: A retrospective chart analysis conducted at UPMC Children’s Hospital of Pittsburgh included 103 infants who had surgery with CEA. The patients were assigned to Group A (Foley catheter removed before epidural discontinuation), Group B (Foley catheter removed after epidural discontinuation), and Group C (no Foley catheter placement). Data collected included demographics, details regarding urinary complications, epidural analgesia, pain management, and Foley catheter management. Results: The median/IQR age was 8 weeks (0.71–13.29), and the weight was 3.01 (2.55–3.52) kg. POURs occurred shortly after surgery in two (1.9%) infants with no initial Foley catheter placement (p = 0.101). Two (1.9%) infants in Group B developed a UTI (p = 0.327). A total of 10 (9.7%) (Groups A and B) had a preexisting urologic condition (p = 0.040). Common surgeries included exploratory laparotomy with bowel resection (34%) and stoma closure (28.2%). The epidural catheter was discontinued on postoperative day 3 (median) (p = 0.587). Total opioid administration, median/IQR (MME mg/kg), was significantly higher in Group B (1.7/0.6–3.8) and Group A (0.7/0.3–1.8) compared to Group C (0.6/0.3–1.1) (p = 0.029). Conclusions: No POUR occurred when the Foley catheter was removed before the epidural was discontinued. UTIs occurred when the Foley catheter remained after epidural discontinuation. Our findings highlight the importance of individualized assessment for urinary catheter placement and early removal in young infants receiving CEA.